A STUDY ON TEACHING READING COMPREHENSION BY USING SHORT STORY AT THE SEVENTH GRADE OF MTS MANSHURUL UMMAH PASEAN PAMEKASAN - Zainollah Zainollah (Kariman: Jurnal Pendidikan dan Keislaman, 2017)
This study has three research focuses: (1) how does the English teacher teach reading comprehension by using short story, (2) what are the obstacles faced by English teacher, and (3) what are the advantages of teaching reading comprehension by using shot story at the seventh grade of MTs Manshurul Ummah Pasean Pamekasan. The approach of this study is qualitative and the kind is descriptive. The data was collected through observation, interview and documentation and analyzed by using explorative descriptive procedures: data reduction, data display, data conclusion drawing and verification. The data validity used triangulation of data collection techniques. The findings of the study shows: (1) The steps in teaching reading comprehension by using short story are: pre-teaching, whilst-teaching, and post teaching. The use of short story makes students enjoyed learning and students’ are highly motivated, fun and joyfull with the teaching and learning. (2) The obstacles faced by teacher in teaching reading comprehension are: (a) students’ motivation is low, (b) students’ vocabulary is very limitted, (c) students’ self confidence and bravery are very poor. (3) The advantages of teaching reading comprehension are: (a) recognizing English texts genre, (b) increasing fluency in reading, (c) enlarging students’ English vocabulary.